Evaluation of the Effect of Melissa officinalis L. on Cognitive Impairments in major Depressive Disorder Patients Treated with Electroshock Therapy: A Randomized Clinical Trial - Nikfarjam, Masoud; Torabi, Kimia; Kaviani, Fatemeh; Baratpour, Iraj; Raeisi, Hadi; Lorigooini, Zahra (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: Cognitive disorders are among the most common complications of electroconvulsive therapy (ECT) in patients with major depression. The present study aimed to evaluate the effect of Melissa officinalis L. (lemon balm) capsules on cognitive impairments in depressed patients treated with ECT. Methods: This randomized clinical trial was conducted on 70 patients with significant depression undergoing ECT. Intervention groups were treated with medicinal capsules containing 500 mg of dried M. officinalis leaf powder administered three times a day, and the control group received wheat starch capsules as a placebo administered three times a day. Data were analyzed using independent t-tests, repeated measures ANOVA, and Bonferroni post-hoc tests with SPSS version 24. Results: There was no statistically significant difference between demographic variables between groups (P>0.05). The MMSE score before the intervention was 24.46±2.11 and 24.86±2.14 in the intervention and control groups, respectively. After the intervention, the MMSE scores were 24.21±2.12 and 24.10±2.26 in both groups, respectively. The MMSE score at the follow-up in the intervention and control groups was 24.66±2.09 and 25.71±1.97, respectively. Moreover, there was no significant interaction between the group and MMSE before the intervention, after the intervention, and at the follow-up (P=0.356). Conclusion: The administration of dried M. officinalis leaf powder demonstrated no significant effect on improving cognitive impairments after ECT. Therefore, the use of the M. officinalis leaf extract capsule for cognitive impairments after ECT in more extended treatment periods should be examined in future studies.